Implementation and design of a CLIL curriculum in a suburban school (2023)
Language teachers face constant changes and challenges, lack of learner’s motivation, insufficient preparation, and deficit of syllabus and materials designed with an emphasis on the students' specific needs and settings may make it difficult to achieve an efficient and well-built second language teaching process. This research project will explore and propose how CLIL may encourage L2 learning with meaningful and diverse content by using it as a means of learning a foreign language.